2006
DOI: 10.1192/bjp.bp.104.007773
|View full text |Cite
|
Sign up to set email alerts
|

Prospective 12-month course of bipolar disorder in out-patients with and without comorbid anxiety disorders

Abstract: Anxiety disorders, including those present during relative euthymia, predicted a poorer bipolar course. The detrimental effects of anxiety were not simply a feature of mood state. Treatment studies targeting anxiety disorders will help to clarify the nature of the impact of anxiety on bipolar course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
155
1
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 194 publications
(176 citation statements)
references
References 27 publications
16
155
1
4
Order By: Relevance
“…In particular, with respect to BD, anxiety disorders are associated with earlier age of onset, poorer treatment response (Feske et al, 2000), exacerbated illness course and severity (Goodwin and Hoven, 2002;Boylan et al, 2004;Keller, 2006;Otto et al, 2006), and suicidality (Dilsaver and Chen, 2003). Previous studies have also demonstrated that anxiety disorders among youth are significant predictors of later BD in adulthood (Goodwin and Hamilton, 2002;Johnson et al, 2000;Kessler et al, 1997;Kim-Cohen et al, 2003;Perugi et al, 2001), and anxiety disorders predate BD among most youth with comorbid anxiety disorders and BD (Dickstein et al, 2005;Dilsaver and White, 1986;Masi et al, 2001;Wagner, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, with respect to BD, anxiety disorders are associated with earlier age of onset, poorer treatment response (Feske et al, 2000), exacerbated illness course and severity (Goodwin and Hoven, 2002;Boylan et al, 2004;Keller, 2006;Otto et al, 2006), and suicidality (Dilsaver and Chen, 2003). Previous studies have also demonstrated that anxiety disorders among youth are significant predictors of later BD in adulthood (Goodwin and Hamilton, 2002;Johnson et al, 2000;Kessler et al, 1997;Kim-Cohen et al, 2003;Perugi et al, 2001), and anxiety disorders predate BD among most youth with comorbid anxiety disorders and BD (Dickstein et al, 2005;Dilsaver and White, 1986;Masi et al, 2001;Wagner, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Among residual symptoms, insomnia and anxiety are most commonly observed and predict a poor course of bipolar disorder (Otto et al, 2006;Putnins et al, 2012); however, evidence for treatment options is limited. Insomnia and anxiety are typically treated with the adjunctive benzodiazepines, which risk abuse and dependency if used chronically (Uzun et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In our study the same relationship exists in the context of the comorbidities. Both co-morbid anxiety (Otto et al 2006) and personality disorders (George et al 2003) have been found to modify the course of bipolar disorder, which reflects in worse marital functioning as well and should be taken into consideration. What is interesting, both of these factors turned out to be insignificant in the context of dyadic cohesion.…”
Section: Discussionmentioning
confidence: 99%